PENERAPAN METODE PEMBERIAN TUGAS UNTUK PERKEMBANGAN KOGNITIF ANAK USIA 5-6 TAHUN DI TK IMMANUEL - Eugenie, Olivia Esty; Ali, Muhamad; Yuniarni, Desni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis research was aimed to describe the implementation of the assignment methodfor cognitive development on 5-6-year-old children in the Kindergarten of Kristen Immanuel I Pontianak Selatan. The research method used was descriptive with aqualitative approach. The subject of research was the teachers and studentsof Kindergarten of Kristen Immanuel I Pontianak Selatan. The data were collectedusing observation, interviews, and documentation techniques. The instruments used for data collection were observation guidelines, interview sheets, and documentation tools. The findings showed that the implementation of the selected method has been employed in accordance with the steps in carrying out the activities and tasks given related to the cognitive development of children. Thus, in applying the assignment method, it is suggested that teachers should pay more attention to children who tend to be busy themselves, provide a variety of media so that children do not feel bored, and add play tools that support the learning. Keywords: Assignment Method,  Cognitive Development